Finiteness Conditions for Strictness Analysis - Nielson, Flemming; Nielson, Hanne Riis (DAIMI Report Series, 1993)
We give upper bounds on the number of times the fixed point operator needs to be unfolded for strictness analysis of functional languages with lists. This extends previous work both in the syntax-directed nature of the approach and in the ability to deal with Wadler's method for analysing lists. Limitations of the method are indicated.